Telaah Teoretis dan Yuridis Tukar Menukar Barang Milik Daerah dengan Swasta - umbu rauta; Titon Slamet Kurnia; Arie Siswanto (Jurnal Hukum IUS QUIA IUSTUM, 2017)
This study brought up the problems, first, the theoretical foundation of the exchange of regional owned property (BMD) between local government and private parties. Second, the laws and regulations governing the exchange activities of BMD. Third, basic considerations in relation to the exchange of BMD. The type of the research was normative research. The results concluded that, first, theoretically, the government (local government) can do contractualization of governmentaffairs because this has become a practice (habit) in the government. The contractualisation includes exchange agreements with non-governmental parties that involve assets(land)thatare under government control (BMD). Second, juridically, the regulational basis for the exchange agreement serving as the basis for the right to transfer the assets (land) under government control (BMD) can be found in the legislation. In doing such actions, terms and conditions of legislation shall apply as the basis of the validity of the actions which includes the aspects of authority, substance and procedure. Third, another thing that determines the feasibility of government action in exchanging BMD (in the form of land) is the aspect of benefit (doelmatigheid).